Respuesta :
2x - y = -2 . . . (1)
5x - 2y = -7 . . . (2)
From (1), y = 2x + 2 . . . (3)
Putting (3) into (2), gives:
5x - 2(2x + 2) = -7
5x - 4x - 4 = -7
x - 4 = -7
x = -7 + 4 = -3
y = 2(-3) + 2 = -6 + 2 = -4.
Therefore, the required answer is (-3, -4)
5x - 2y = -7 . . . (2)
From (1), y = 2x + 2 . . . (3)
Putting (3) into (2), gives:
5x - 2(2x + 2) = -7
5x - 4x - 4 = -7
x - 4 = -7
x = -7 + 4 = -3
y = 2(-3) + 2 = -6 + 2 = -4.
Therefore, the required answer is (-3, -4)
2 x - y = - 2 / * ( - 2 )
5 x - 2 y = - 7
--------------------
- 4 x + 2 y = 4
+
5 x - 2 y = - 7
------------------------
x = - 3
- 15 - 2 y = - 7
- 2 y = - 7 + 15
- 2 y = 8
y = 8 : ( - 2 ) , y = - 4
Answer: A ( - 3 , - 4 )
5 x - 2 y = - 7
--------------------
- 4 x + 2 y = 4
+
5 x - 2 y = - 7
------------------------
x = - 3
- 15 - 2 y = - 7
- 2 y = - 7 + 15
- 2 y = 8
y = 8 : ( - 2 ) , y = - 4
Answer: A ( - 3 , - 4 )